Qualitative Platelet 12-Lipoxygenase Abnormality in a Patient with Essential Thrombocythemia - Tomo, Kenjiro; Takayama, Hiroshi; Kaneko, Yoshiyuki; Fujita, Jun; Nakamura, Michihiro; Ueda, Natsuo; Yamamoto, Shozo; Okuma, Minoru (Thrombosis and Haemostasis, 1997)
Quantitative platelet 12-lipoxygenase (12-LOX) deficiency has been reported in some patients with myeloproliferative disorders (MPD). We report here for the first time a novel qualitative abnormality of the 12-LOX enzyme of platelets from a patient with essential thrombocythemia. The anti-12-LOX immunoprecipitates from the patient’s platelet homogenates showed a deficiency of 12-LOX activity, but contained normal amount of 12-LOX protein. There was no difference in subcellular localization of the enzyme between the patient’s platelets and normal ones. This 12-LOX protein lacking its enzyme activity showed slightly larger electrophoretic mobility than normal one, suggesting a molecular abnormality of the enzyme. However, we could not detect any genetic mutation causing such abnormalities in all exons of 12-LOX gene by sequencing the patient’s PCR-amplified DNA. Thus, our results indicate that the deficient activity of this abnormal 12-LOX protein is probably due to a posttranslational modification, and the possibility that platelets of some MPD patients have qualitative abnormality of the 12-LOX enzyme besides quantitative one.